2021
DOI: 10.3390/ani11113247
|View full text |Cite
|
Sign up to set email alerts
|

Role of Innate Immunity in Initiation and Progression of Osteoarthritis, with Emphasis on Horses

Abstract: Osteoarthritis (OA) is a common condition with diverse etiologies, affecting horses, humans, and companion animals. Importantly, OA is not a single disease, but rather a disease process initiated by different events, including acute trauma, irregular or repetitive overload of articular structures, and spontaneous development with aging. Our understanding of the pathogenesis of OA is still evolving, and OA is increasingly considered a multifactorial disease in which the innate immune system plays a key role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…While an imbalance between cartilage degradation and new matrix synthesis leading to cartilage damage is considered central to the pathogenesis of OA, the involvement of an inflammatory component has now been well-recognized. Recent literature suggests that an innate immune response mediated by the joint components such as synovial membrane, joint capsule, subchondral bone and ligaments is responsible for initiating and sustaining an immune-mediated inflammation in the diseased joint ( 38 41 ). It is important to recognize that early inflammation, in response to joint injury is beneficial for the repair process.…”
Section: Principles Of Gene Therapymentioning
confidence: 99%
“…While an imbalance between cartilage degradation and new matrix synthesis leading to cartilage damage is considered central to the pathogenesis of OA, the involvement of an inflammatory component has now been well-recognized. Recent literature suggests that an innate immune response mediated by the joint components such as synovial membrane, joint capsule, subchondral bone and ligaments is responsible for initiating and sustaining an immune-mediated inflammation in the diseased joint ( 38 41 ). It is important to recognize that early inflammation, in response to joint injury is beneficial for the repair process.…”
Section: Principles Of Gene Therapymentioning
confidence: 99%
“…In this study, we first reported a significant increase in TGF-β1 and VEGF in ACS of the OA dogs compared to the sham plasma control, similar to the previous report in human OA [ 16 ]. These growth factors are believed to play a role in joint homeostasis [ 25 ] and vascular regeneration [ 8 , 38 ], which are essential for joint and tendon repairs [ 36 , 39 ]. However, previous reports investigating ACS in normal dogs did not find the differences in these cytokines when compared to the normal serum [ 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using autologous bioactive agents enriched in anti-inflammatory mediators and growth factors for tissue regeneration has become a novel insight for OA management [ 11 , 23 ]. Apart from the IL-1 receptor modulation, several recent studies suggest that T cell-mediated response plays a significant role in the aggravation of OA, including an increase in activated T cells in synovial fluid and synovial membrane [ 24 , 25 ]. As a result, the immune mediated degeneration of the joint prevents the healing process.…”
Section: Introductionmentioning
confidence: 99%
“…Synovial fluid in a healthy joint contains no or few immune cells. The synovium is the most critical joint structure in its ability to mount an inflammatory response [25]. Neutrophils are the most common immune cell found in inflamed joint synovial fluid.…”
Section: Trafficking Of Circulating Blood Neutrophils To the Synovial...mentioning
confidence: 99%